Judicialização do direito à saúde: um estudo da assistência farmacêutica na região metropolitana de Santarém - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This dissertation aims to analyze the phenomenon of judicialization of the right to health, especially with regard to the supply of medicines, in the Court of Justice of the State of Pará - Comarca de Santarém, headquarters of the metropolitan region of Santarém, in the west of Pará. The study precedes an interdisciplinary approach, which rescues the historical conception of health, the evolution of fundamental social rights; it deals with the right to health; the Unified Health System and seeks to elucidate the elements involved in the phenomenon of judicialization of health in the provision of pharmaceutical care. This is a bibliographic and documentary study, with a mixed quantitative and qualitative approach. The bibliographic research was developed from a Systematic Literature Review (RSL) in the scopus database of works related to judicialization, right to health and supply of medicines. The documentary research is exploratory and descriptive, applying the content analysis of Bardin (2017) for the treatment of data produced from legal proceedings in the District of Santarém in the period between 2018 and 2021, the sample has 34 analyzed processes, in which it was possible to present some characteristics, among them: predominance of individual litigation; curative focus of demands; tendency to grant early injunction; little mention of the statements of the National Council of Justice; no prior consultation with the Technical Advisory Center and predominance of medication requests not covered by public policies. Data analysis also shows a range of literature focused on research on the judicialization of the right to health, however, it was concluded that it is necessary to stimulate a multidisciplinary debate between health managers, medical professionals and legal practitioners, especially in around the new contours, discussions and proposals that emerged after the work of the National Council of Justice, in the sense of promoting the sustainability and rationality of the judicialization of health. Despite this being a viable alternative for the realization of the individual's right to health, it is a controversial topic, as it does not effectively reach public health policies.
Keywords: Judicialização; Direito à saúde; Sistema Único de Saúde; Medicamentos; Amazônia paraense; Políticas Públicas, Diversidade Cultural e Desenvolvimento Amazônico.